DIAGNÓSTICO DAS DIARREIAS INFECCIOSAS EM BEZERROS NOS BIOMAS CERRADO E PANTANAL SUL-MATO-GROSSENSE - Juliane Francielle Tutija (2024)
Diarrhea in calves is one of the main causes of economic losses with high morbidity and mortality in the livestock industry worldwide. Enteropathogens of bacterial, parasitic and viral origin may be involved, isolated or in association. Escherichia coli, Salmonella spp., Rotavirus, Coronavirus, protozoa of the genera Eimeria spp. and Cryptosporidium spp., are among the main agents. Other possible agents causing diarrhea are Nobovirus, Norovirus and Enterovirus. The Pantanal and the Cerrado of Mato Grosso do Sul are among the main areas of agricultural exploration in Brazil. Therefore, this work aimed to evaluate the potential of bacterial, viral and parasitic agents to cause diarrhea in calves in these regions. Between 2019 and 2023, 456 fecal samples were collected from calves in the Pantanal and Cerrado biomes in the state of Mato Grosso do Sul, Brazil. All samples were subjected to microbiological analysis and antimicrobial susceptibility testing (AST). Bacterial growth was observed in 451 of 456 samples, and these E. coli were identified biochemically. All 451 isolates (100%) exhibited some phenotypic resistance to antimicrobials, and 67.62% exhibited multidrug resistance. The frequency of multidrug-resistant isolates in the Cerrado biome was significantly higher than in the Pantanal biome (p = 0.0001). In the Cerrado, the most common pathotype was Shiga toxin-producing E. coli (STEC) (28%), followed by toxigenic E. coli (ETEC) (11%), enterohemorrhagic E. coli (EHEC) (8%) and enteropathogenic E. coli (EPEC) (2%). In most cases, the concomitant occurrence of pathotypes was more common, the most common being ETEC + STEC (33%), ETEC + EHEC (15%) and ETEC + EPEC (3%). The STEC pattern (30%) was also found most frequently in the Pantanal, followed by EHEC (12%), ETEC (9%) and EPEC (6%). The STEC pathotype showed a significantly higher frequency of multidrug resistance (p = 0.0486) compared to other identified pathotypes. For Cryptosporidium sp. 310 samples were evaluated using the PCR technique, with only two (0.64%) obtaining positive results. In the RT-PCR analysis of 269 samples evaluated, all were negative for Rotavirus, Coronavirus, Enterovirus, Nebovirus, Norovirus, Kobuvirus and Pestivirus. In the classification and identification of Eimeria sp., the most frequent species was E. zuernii, being present in all samples (pools) with or without diarrhea, followed by E. ellipsoidalis present in three of the six pools (50%) with a load parasitic load of this species which ranged from 4 to 84% and E. bovis present in three of the six pools (50%) with a parasitic load of 8 to 27%. With the results obtained in the present study, it was identified that the infectious agents involved in diarrhea were mainly E. coli with pathogenic and multiresistant pathotypes and Eimeria spp. pathogenic.